Stereoscopic Depth of Field: Why we can easily perceive and distinguish the depth of neighboring objects under binocular condition than monocular - Park, Min-Chul; Lee, Kwang-Hoon (THREE-DIMENSIONAL IMAGING, VISUALIZATION, AND DISPLAY 2016, 2016)
This work reinterprets the roll of depth of field in stereoscopy. In binocular condition two regions of DOFs make a superposed area with lozenge shape. Characteristic of area will be a hint for understanding the reason why we can easy perceive and distinguish the depth in neighboring objects under the binocular condition than the monocular. To verify the reason we proposed a concept which called as the stereoscopic depth of field (SDOF). Consequently SDOF showed the narrowed superposed area has higher the depth distinguishable power than the widen area. The power is also proportional to the converging angle increment.